Whether and when to liberalize capital account and financial services - John Williamsonn; Zdenek Drabek (World Trade Organization (WTO), 1999)
Discussions about international capital movements raise extremely important and controversial questions. Why should countries open up their capital accounts, especially considering that unrestricted international capital movement is a relatively new phenomenon? For example, many OECD countries have not eliminated their foreign exchange restrictions only until the 1980's. If the answer is unequivocally affirmative, does it matter how fast should countries do so? Should they wait until all essential pieces of the policy package are in place before they eliminate all restrictions? How are international capital movements related to domestic financial sectors? Is there a difference between opening to competition an industry such as car manufacturing as compared to the banking sector? Should the opening of the banking sector be governed by different rules? Rules about foreign exchange restrictions are already in place in the IMF Articles. Until recently, the IMF Articles only called for the elimination of foreign exchange restrictions on the current account. The ongoing discussion and the controversy about globalization that calls for the capital account liberalization introduces, therefore, a relatively new element into the whole discussion. These questions have also implications for the World Trade Organization. It is well known, that the Uruguay Round Agreements have already provided a coverage for a number of aspects that are directly related to foreign investment. Rules established elsewhere such as in the context of changes to the IMF Articles will obviously have an important bearing for the implementation of rules agreed in the Uruguay Round. This raises a variety of other questions in the mind of some observers. Who should decide about the rules on capital account liberalization? What rules? IMF? What is the role of the WTO? How does one link the two? All of the questions raised above are clearly extremely important and most of them are discussed in the following paper by John Williamson. Mr. Williamson's presentation is based on his lecture and discussion which was delivered on 17 June 1999 at the WTO. The actual text that follows is a transcript of that lecture.
Keywords: F31; F32; 330; Capital Movements; Capital Account Restrictions; Financial Services